A counterfactual economic analysis of Covid-19 using a threshold augmented multi-country model. (December 2021) - Chudik, Alexander; Mohaddes, Kamiar; Pesaran, M. Hashem; Raissi, Mehdi; Rebucci, Alessandro
Highlights: We detect threshold effects in the relationship between GDP growth and excess global volatility. We quantify the macroeconomic effects of Covid-19 using a threshold-augmented GVAR model. We show that Covid-19 can have large and persistent negative effects on the world economy But the outcomes vary substantially across countries and regions. We show that no country is immune to the economic fallout of the pandemic. Abstract: This paper develops a threshold-augmented dynamic multi-country model (TGVAR) to quantify the macroeconomic effects of the Covid-19 pandemic. We show that there exist threshold effects in the relationship between output growth and excess global volatility at individual country levels in a significant majority of advanced economies and several emerging markets. We then estimate a more general multi-country model augmented with these threshold effects as well as long term interest rates, oil prices, exchange rates and equity returns to perform counterfactual analyses. We distinguish common global factors from trade-related spillovers, and identify the Covid-19 shock using GDP growth projection revisions of the IMF in 2020Q1. We account for sample uncertainty by bootstrapping the multi-country model estimated over four decades of quarterly observations. Our results show that, without policy support, the Covid-19 pandemic would cause a significant and long-lasting fall in world output, with outcomes that are quite heterogenous across countries and regions. While the impact on China and other emerging Asian economies are estimated to be less severe, the United Kingdom, and several other advanced economies may experience deeper and longer-lasting effects. Non-Asian emerging markets stand out for their vulnerability. We show that no country is immune to the economic fallout of the pandemic because of global interconnections as evidenced by the case of Sweden. We also find that long-term interest rates could temporarily fall below their pre-Covid-19 lows in core advanced economies, but this does not seem to be the case in emerging markets.